TREE SPECIES DIVERSITY IN PHRA THAT SI MUEANG PONG AREA, CHIANG MAI PROVINCE, THAILAND - Pongpan Leelahakriengkrai; Akharasit Bunsongthae; Audcharapat Insing (Biotropia: The Southeast Asian Journal of Tropical Biology)
Article Highlights - Rich tree diversity found in Phra That Si Mueang Pong area. - Endangered species identified, promoting conservation efforts. - Unique plant distribution influenced by land use and water proximity. - Potential for ecotourism and environmental education in the region. - Study provides foundational data for future ecological research.